Hepatocellular carcinoma progression is protected by miRNA-34c-5p by regulating FAM83A - Yu, W-S; Wang, Z-G; Guo, R-P; Lin, Z-Q; Ye, Z-W; Lu, C-L (European review for medical and pharmacological sciences, 2020)
To elucidate the role of microRNA-34c-5p (miRNA-34c-5p) in the progression of hepatocellular carcinoma (HCC) and the indicated mechanism. Relative levels of miRNA-34c-5p and FAM83A in HCC tissues and cell lines were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Their influences on clinical features in HCC patients were analyzed. Kaplan-Meier method was introduced for assessing the relationship between miRNA-34c-5p and overall survival in HCC. After overexpression of miRNA-34c-5p in HepG2 and HB611 cells, we detected proliferative, migratory and invasive abilities by cell counting kit-8 (CCK-8) and transwell assay. The interaction between miRNA-34c-5p and FAM83A was explored by Dual-Luciferase reporter assay. Finally, their co-regulation on HCC cell phenotypes was examined. MiRNA-34c-5p was downregulated in HCC tissues, especially stage III+IV cases. Its level was correlated to tumor size, tumor number and TNM staging in HCC. Overexpression of miRNA-34c-5p inhibited proliferative, migratory and invasive abilities in HepG2 and HB611 cells. In addition, miRNA-34c-5p targeted on FAM83A and negatively regulated its level. Overexpression of FAM83A could reverse the inhibitory effects of miRNA-34c-5p on malignant phenotypes of HCC cells. By negatively regulating FAM83A level, miRNA-34c-5p alleviates the progression of HCC.